Efficiency of corn cultivation to enhance food self-sufficiency in Indonesia (Revista de Ciências Agroveterinárias, 2024)
Corn farming is crucial for achieving national food self-sufficiency in Central Java Province, as it contributes to structural changes in the economy. This research aims to evaluate the effectiveness of the methods used and study the factors involved in the production of corn. A Stochastic Frontier (SFA) model assessed efficiency and production factors. The findings indicate that farmers operate at a technical efficiency of 77%, an allocative efficiency of 63%, and an economic efficiency of 56%. To enhance efficiency, farmers are encouraged to optimize corn farming inputs. Notably, the production factors of land area, seeds, urea fertilizers, NPK fertilizers, KCI fertilizers, pesticides, and labor show positive effects. The evaluation of business size suggests that there are growing returns to scale, emphasizing the beneficial effect of increasing production inputs on the production of corn. However, neglecting production factors may lead to additional inputs and reduced crop yields. Optimizing the use of inputs can lead to increased production scale in corn farming, improved efficiency, and national food self-sufficiency. This research can provide valuable insights for farmers to enhance efficiency through the effective use of inputs. Moreover, the findings are instrumental in the government's development of agricultural plans aimed at advancing farming and implementing policies to boost efficiency and attain food self-sufficiency.
Keywords: performance evaluation; corn farming efficiency; food self-sufficiency; production factor; stochastic frontier analysis